Adsorption kinetics and thermodynamics of water-insoluble crosslinked β-cyclodextrin polymer for phenol in aqueous solution - Huang, Hui; Fan, Yifan; Wang, Junwei; Gao, Haoqi; Tao, Shiying (Springer, 2013)
A water-insoluble β-cyclodextrin (β-CD) polymer was synthesized by reacting β-CD with hexamethyl- ene diisocyanate, and its adsorption kinetics and thermodynamics for phenol from aqueous solution was investi- gated. The kinetics of adsorption followed the pseudo-second-order model and the adsorption isotherms could be well fitted by the Freundlich adsorption equation. The values of thermodynamic parameters demonstrated that the adsorption was a physisorption in a spontaneous and exothermic process.